STENTING PADA SINUS VENOSUS SEREBRAL DENGAN HIPERTENSI INTRAKRANIAL IDIOPATIK - Fritz Sumantri Usman,* Gamaliel Wibowo Soetanto,** Pinto Desti Piliang,** Audhy Tanasal,** Hernawan (NEURONA, 2018)
INTRACRANIAL HYPERTENSION IIH IS A GROUP OF SYMPTOMS CAUSED BY INCREASE IN INTRACRANIAL PRESSURE WITHOUT ANY DAMAGE OF BRAIN PARENCHYMA IDIOPATHIC INTRACRANIAL HYPERTENSION IS USUALLY KNOWN AS CEREBRAL PSEUDOTUMOR THIS DISEASE CAN CAUSE VISUAL DISTURBANCE EVEN VISUAL LOSS THUS DECREASE QUALITY OF DAILY LIVING TREATMENT OF THIS DISEASE CONSISTS OF DISEASE MODIFYING MEDICINE SURGERY AND NEUROVASCULAR INTERVENTIONAL PROCEDURE SUCH AS VENOUS SINUS STENTING